PROFIL MOTIVASI UNTUK MELANJUTKAN PENDIDIKAN KE PERGURUAN TINGGI SISWA KELAS XII SMAN 4 GARUT - Ernawati, Dwi; Wikanengsih, Wikanengsih; Alawiyah, Tuti (IKIP Siliwangi, 2020)
This study aims to get an overview and to understand in depth about the motivation to continue education to higher education students of class XII SMAN 4 Garut. The approach in this research is descriptive quantitative. Retrieval of data using the interview method. The subjects in this study were 5 students. The results of this study indicate that the factors inhibiting participants in continuing their studies to higher education include: Lack of interest in student learning towards education and higher education, lack of motivation from parents to improve their children's education, high costs of education in tertiary institutions and the economic condition of parents who insufficient or even inadequate, the requirements set by the desired tertiary institution are not fulfilled, and the community does not care less about education.Keywords:Â Â Motivation, Education to collegeÂ